Use of psychotropic drugs for neuropsychiatric symptoms in patients hospitalized with COVID-19 - Valdivieso-Jiménez, Glauco (2021)
COVID-19 pandemic is the current global health crisis that, to date, has claimed thousands of lives in most countries. Since the beginning of 2020, the epidemiological and clinical behavior of the SARS-CoV-2, as well as proposals for therapeutic schemes that address the elimination of this virus per se and its complications at the systemic level, have been studied. However, neuropsychiatric symptoms also occur in patients hospitalized for this infection, so pharmacological management requires special considerations at the time of prescription. The most common neuropsychiatric symptoms secondary to COVID-19 infection are anxiety, insomnia, depressed mood, delirium and agitation. The choice of psychotropic drugs requires to be based on the principle of not generating more harm, and assessing the risk-benefit, pharmacological profile, possible interactions and previous medical conditions of the patient.